A Checklist of Molluscs of Glacier National Park, Montana - Richard H. Russell; Royal Bruce Brunson (Hello World!, 1967)
Several aspects of the natural history of Glacier park have been studied, and pamphlets have been printed which dealt with such well known areas as wild-flowers, birds, mammals and rocks. However, little has been published on the invertebrate faunas, and except for the work of S. S. Berry in 1919, no survey has been made of the Mollusca.